Do distressed firms manage earnings? - Dian Anita Nuswantara; Warih Puspo Andjani (Jurnal Siasat Bisnis, 2021)
Purpose: This research aims to test and analyze whether the central role of SOE compare with the phenomenon of financial distress will result in dysfunctional behavior. This motivates researchers to investigate SOE financial performance and behavior. Thus, this study aims to prove that the influence of financial distress on SOE and POE behavior is different.Design/methodology/approach: The researcher employs a quantitative approach to test the hypotheses. The data collected using documentation of financial data of 55 SOE and 135 POE listed in Indonesia Stock Exchange year 2014-2018. Distress status determines using Altman Z-score and earnings management measured using the Modified Jones Model. This study examines two groups of samples originating to test hypotheses using two independent sample t-tests.Findings: The research results succeeded in proving that SOE and POE react to a distressing condition in different ways. While SOE responds in the increasing pattern, means income maximization, the POE were in the opposite direction.Research limitations/implications: Scoring bankrupt prediction use only one equation, that is Altman Z-score, thus there are bias potential due to “no one-size-fits-all” view point.Practical implications: This result suggests that the government and other shareholders should be careful in making decisions concerning distressed SOE.Originality/value: Most earnings study was conducted in good financial performance in order to get a general conclusion. Since other scholars focus on how SOE performance in a “normal” situation, this research tries to investigate their behavior in the “abnormal situation.